Шкільна освіта на Ровенщині в перші повоєнні роки - Мащенко, Наталія; Mashchenko, Nataliia (Східноєвропейський національний університет імені Лесі Українки, 2014)
Досліджується процес становлення радянської системи шкільної освіти в Ровенській області у перші повоєнні роки, аналізуються форми і методи відбудови матеріально-технічної, навчальної бази шкіл, розглядаються основні заходи щодо забезпечення загальноосвітніх закладів краю вчительськими кадрами.

In article considered the process of incipience soviet system of school education in Rivne region during first years of postwar rebuilding. We analyzed forms and methods of reconstruction material and training base's in the schools, investigated changes in structure of education edge of the region, highlights the problem of supplying schools by qualified teachers. Despite the difficulties, in first years was established soviet unified education system. In short period were restored the work of most schools in region. However, they didn't resolved the question of supplying education base and the problem of a teacher. Basis of the article was a State archive of Rivne region, and also works of soviet and modern historians.
School Education in Rovno Region During First Years of Postwar Rebuilduing
Keywords: радянізація; шкільна освіта; закон про всеобуч; кадрова політика; sovietization; school education; law on compulsory general education; HR policy